Evolution, Development and Ecology of Anemonefishes : Model Organisms for Marine Science. - Laudet, Vincent. (Taylor & Francis Group, 2022)
Anemonefishes, one of the most popular and recognizable of fishes in the world, are much more than film characters, they are also emerging model organisms for studying the biology, ecology and evolution of coral reef fishes.